Small deep hole drilling electro discharge machining process optimization using Taguchi method - Jiménez-Chavarro, Guillermo; Vieira-Porto, Arthur José; Hideaki-Tsunaki, Roberto (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Small deep hole drilling in high hardness metals is an operation beyond the reach of the conventional drilling machine process, and one of the most suitable processes for this operation is the Electro Discharge Machining, EDM. Due to the numerous variables involved in electro discharge machining and the restrictions imposed by the small size, it is necessary to determine the precise adjustment level for each of the variables in order to reach an efficient and good quality machining process.This paper shows how using a Taguchi L27 orthogonal arrangement, the cleaning effect of the electrical variables, and the electrode diameter on the machining characteristics of small diameter holes in a DIN 1.3344 work piece, made it possible to be analyzed. The experimental analysis results and their data turned into noise signals, allowed to optimize the material removal rate, the feed rate drilling speed, the electrode wear and the surface roughness.